A CLASSIFICATION OF SEMISYMMETRIC CUBIC GRAPHS OF ORDER 28p&sup2 - Alaeiyan, Mehdi; Lashani, Mohsen (Journal of the Indonesian Mathematical Society, 2010)
A graph is said to be semisymmetric if its full automorphism group actstransitively on its edge set but not on its vertex set. In this paper, we prove thatthere is only one semisymmetric cubic graph of order 28psub2/sub, where p is a prime.DOI :Â http://dx.doi.org/10.22342/jims.16.2.38.139-143